Nanomechanical Sensors as a Tool for Bacteria Detection and Antibiotic Susceptibility Testing - Pujol-Vila, Ferran; Villa, Rosa; Alvarez, Mar (Frontiers in Mechanical Engineering, 2020)
Nanomechanical biosensors refers to a subfamily of micro-electromechanical systems (MEMS) consisting in movable suspended microstructures, able to convert biological processes into measurable mechanical motion. Owing to this, nanomechanical biosensors have become a promising technology in the way to detect and manage bacterial pathogens with improved effectiveness. The precise treatment of an infection relies on its early diagnosis; however, the current standard culture-based methods for bacteria detection and antibiotic susceptibility testing involve long protocols and are labor intensive. Thanks to its high sensitivity, fast response, and high throughput capability, the nanomechanical technology holds great potential for overcoming some of the limitations of conventional methods. This review aims to provide a perspective of the diverse transducer structures, working principles and detection strategies of nanomechanical sensors for bacteria detection and antibiotic susceptibility testing. Their performance in terms of sensitivity and operation time is compared with standard methods currently used in clinical microbiology laboratories. Besides, commercial systems already developed and challenges in the way to reach real sensing application beyond the research environment are discussed.